Pengaruh Environmental, Social dan Governance Disclosure Terhadap Profitabilitas Perusahaan - Wijaya, Rano; Syaiful Hifni; Saprudin; Isnawati; Nordiansyah, M. (Universitas Lambung Mangkurat, 2025)
Profitability is one of the main objectives in establishing a company, with the end result being increased profits for shareholders. Given the importance of profitability in achieving this goal, research is needed on what factors influence it. Environmental, social, and governance disclosures will be measured for their impact on profitability. Environmental disclosure is measured using the PROPER Rating, social disclosure is assessed based on the Corporate Social Responsibility Disclosure Index (CSRDI), while governance disclosure is proxied through differences in gender, nationality, and size of the board of directors. This study uses a population of companies that are issuers on the Indonesia Stock Exchange during the 2020-2023 period. In addition, purposive sampling will be used as the basis for selecting samples. This study uses path analysis in testing its hypotheses using SPSS as its statistical tool. The results of the study found that Environment (X1), Gender Diversity (X3), National Diversity (X4), and Board Size (X5) all have a significant effect on ROA. Meanwhile, Social Disclosure (X2) does not have a significant effect in this model. Improvements in environmental policies, gender diversity, and national diversity have a positive effect on the company's financial performance. Larger board sizes tend to reduce financial performance, possibly due to increased complexity in decision making